Data fusion approach for a digital construction logistics twin - Gehring, Maximilian; Rüppel, Uwe (Frontiers in Built Environment, 2023)
Construction site logistics deals with the transport and storage of materials as part of the execution of a construction project. An important part of construction logistics is informing those who are involved in the project about the current status of the ordered materials. On the one hand, the missing overview of the material inventory on the construction site and incoming deliveries makes efficient daily work planning on the construction site more difficult. On the other hand, unnecessary search and travel times reduce the productive working hours of employees on the construction site. In order to provide a better overview, the information from existing data sources must be linked and visualized in an easily understandable way for all project participants. Therefore, a digital construction logistics twin is proposed in this paper. Here, the challenge lies in the creation of the digital twin. The aim of this paper is to reduce the manual entry and planning effort needed. Therefore, an approach is proposed, which uses the Building Information Model (BIM), information from the technical specifications and bill of quantities as well as catalogue data from the building materials trade. The Building Information Model comprises the three-dimensional building model, information about the building components, the construction schedule (4D BIM) and the planned storage spaces on the constructions site. The catalogue data adds relevant logistic attributes and could also enables guidelines to be checked, e.g., as part of a sustainability certification (e.g., LEED). If the suppliers’ telemetry data were integrated, end-to-end material tracking would even be possible, similar to “track-and-trace” services from parcel service providers for end customers. The provision of all this data via a Building Information Model server as a “single source of truth” increases the transparency of the construction and logistics processes for everyone involved in the project. Also, this information would, for example, favor the use of autonomous means of transport, which reduces the need for manpower for transport on the construction site.